Electrochemical Properties of Tin Sulfide Nano-Sheets as Cathode Material for Lithium-Sulfur Batteries - Saleem, Muhammad; Mehboob, Gohar; Ahmed, M. Shafiq; Khisro, Said Nasir; Ansar, M. Z.; Mehmood, Kashif; Rafiqa-Tul-Rasool,; Alamgir, M. K.; Ejaz, Ahsan; Ghazanfar, M.; Hussain, Shahnwaz; Ahmed, Adil; et al. (Frontiers in Chemistry, 2020)
Unprecedented self-assembled hierarchical nano-sheets of SnS were synthesized by hydrothermal method. In a typical reaction, SnCl2.2H2O and Na2S.9H2O were used as reactants. Structural and morphological properties were studied by X-ray diffraction (XRD), and scanning electron microscopy (SEM) while the electrochemical properties were measured by cyclic voltammetry, charge-discharge cycles, and electrochemical impedance spectroscopy (EIS). SEM results showed the 1-D SnS nano-sheets with average thickness around 20 nm. Cyclic voltammogram and charge-discharge spectra showed good cycling stability. All these results showed that SnS nano-sheets are promising candidate material to be used as electrode for Li-S batteries.